Bridging the gap between government-industry-university collaboration through CEO@Faculty programme - R., Azmi; W.F.W., Wan Fakhruddin; R., Che Me; A., Mohd Yusof; W.O.A.S., Wan Ismail; Z., Abal Abas; N., Mohd Abbas; S., Ahmad Sabri; S., Ya'acob (2021)
The government-university-industry relation is a pertinent aspect in developing talents that fulfil the workplace needs. Lack of industry experience among academics may, to certain extent, affect the quality of university graduates. In responding to this issue, the CEO@Faculty programme was initiated by the Ministry of Higher Education Malaysia as part of an initiative to provide opportunities for young lecturers. The six-month industrial attachment programme at multi-national corporations and government-linked companies is hoped to expose the real experience in the industry to the selected young academicians. The impetus of the study is to evaluate the programme's effectiveness and its contributions to its stakeholders (government. university. industry). The data is derived from questionnaires involving 52 Malaysian university lecturers who participated in the programme. The key aspect that was examined includes the type of collaborations that can be established between the CEO@Faculty fellow and the company. The results of the study reveal that the CEO@Faculty programme has a significant impact on strengthening university-industry cooperation. namely knowledge transfer. research grant contribution. graduate industrial training placement and research collaborations. Besides. this study has also successfully increased the level of leadership competence among the CEO@Faculty fellows who participated in the programme. Thus, the programme's success has directly impacted the personality and leadership development among the lecturers, which is hoped to improve the quality of graduates to meet the needs of the industry.